Acordo de sócios na sociedade limitada: existência, validade e eficácia - Kugler, Herbert Morgenstern (2012)
The partners of a limited liability company s negotiate the company s features when they enter into the articles of association, which must observe the limits provided by applicable legislation. However, the articles of association are not the only and exclusive means the partners have for regulating their rights and obligations insofar as they may enter into other contracts, complementary and accessory to the articles of association. Among these complementary agreements, we accent the quotaholders agreement. The quotaholders agreement is the contract entered into by partners of a limited liability company to discipline their rights and obligations, taking into consideration, in varying degrees, the corporate relationship derived from the company. The present study aimed at analyzing the legal regime applicable to the quotaholders agreement, in view of the doctrine that divides agreements in three spheres (existence, validity and effectiveness) and, also, pursuant to applicable legislation, especially regarding the application of Law 6,404/76 to limited liability companies. We conclude that the quotaholders agreement (i) exists when partners of a limited liability company enter into an agreement, in parallel to the articles of association, in order to discipline their rights and obligations; (ii) is valid when it does not violate applicable legislation or the articles of association, nor is used to harm third parties; and (iii) effects, always, the contracting parties and, provided that certain requisites are observed (filing with the company s headquarters and register before the Public Commercial Board), third parties, including the company